Optimalisasi Pemasaran Produk Melalui Penggunaan Digital Marketing Pada Produk Makanan Ringan Tumpi Di Desa Lerep Kabupaten Semarang - Adhi Susano; Aswin Fitriansyah; Tulus Widjajanto; Meida Rachmawati (Universitas 45 Surabaya, 2023)
It is hoped that the community's creativity in managing Tumpi Snack Food Products MSMEs in Lerep Village, Semarang Regency will be able to become an independent and capable community in order to improve the community's economy to address the problem of poverty. According to researchers' opinions and observations, village community empowerment is closely related to community participation in implementing the work program. The roles carried out in mutual cooperation with the village government in order to empower the community through MSMEs include participatory cooperation with plans carried out according to existing regional potential, utilizing all village potential to maintain the sustainability of development areas and developing village potential so that the village community has power or empowerment of its population. This type of research is descriptive research. The approach used is a qualitative approach and a conceptual approach. The data source used is secondary data. Data analysis was carried out descriptively qualitatively. Conclusions were drawn using a deductive method, namely drawing conclusions from general to specific, especially those related to the research topic, namely Optimizing MSME Product Marketing Through the Use of Digital Marketing on Tumpi Snack Food Products in Lerep Village, Semarang Regency. This research resulted in findings that since it was declared as the souvenir center of the Lerep Tourism Village, Karang Bolo is synonymous with Tumpi and Tempe Kripik. Tumpi and tempe kripik are very attached to Karang Bolo village because Tumpi and tempeh kripik are snack foods produced by most of the residents. this hamlet. The process of making tempeh chips and various other chips in Karang Bolo village, from the initial stage to the final stage, is still done traditionally, including the frying method which still uses a wood-fired stove. It is hoped that the community's creativity in managing MSMEs will be able to become an independent and capable community in order to improve the community's economy to address the problem of poverty. According to researchers' opinions and observations, village community empowerment is closely related to community participation in implementing the work program. The roles carried out in mutual cooperation with the village government in order to empower the community through MSMEs include participatory cooperation with plans carried out according to existing regional potential, utilizing all village potential to maintain the sustainability of development areas and developing village potential so that the village community has power or empowerment of its population.